Protein kinase 2 (CK2): a potential regulator of immune cell development and function in cancer. Issue 3 (3rd July 2021) - Husain, Kazim; Williamson, Tanika T.; Nelson, Nadine; Ghansah, Tomar
Abstract: Protein kinase CK2, formally known as casein kinase II, is ubiquitously expressed and highly conserved serine/threonine or tyrosine kinase enzyme that regulates diverse signaling pathways responsible for cellular processes (i.e., cell proliferation and apoptosis) via interactions with over 500 known substrates. The enzyme's physiological interactions and cellular functions have been widely studied, most notably in the blood and solid malignancies. CK2 has intrinsic role in carcinogenesis as overexpression of CK2 subunits (α, α`, and β) and deregulation of its activity have been linked to various forms of cancers. CK2 also has extrinsic role in cancer stroma or in the tumor microenvironment (TME) including the immune cells. However, very few research studies have focused on extrinsic role of CK2 in regulating immune responses as a therapeutic alternative for cancer. The following review discusses CK2's regulation of key signaling events [Nuclear factor kappa B (NF-κB), Janus kinase/signal transducer and activators of transcription (JAK/STAT), Hypoxia inducible factor–1alpha (HIF-1α), Cyclooygenase-2 (COX-2), Extracellular signal-regulated kinase/mitogen-activated protein kinase (ERK/MAPK), Notch, Protein kinase B/AKT, Ikaros and Wnt] that can influence the development and function of immune cells in cancer. Potential clinical trials using potent CK2 inhibitors will facilitate and improve the treatment of human malignancies.